Evolution of Marital and Family Systems and Family Relations from the Perspective of the “Fertility System” - Yi, Yixin; Han, Menglu; Zhao, Yichen (International Journal of Social Sciences and Public Administration, 2024)
Fei Xiaotong pointed out that, from the observable perspective of human society, the fertility system manifests as a series of institutions within marriage and family. “In order to fulfill the function of social reproduction, a series of social institutions such as marriage, family, and kinship emerged, collectively referred to as the ‘fertility system,’ which encompasses the two aspects of reproduction and nurturing, essential activities for maintaining the existence of the group.” Marriage, family, kinship, and other institutional frameworks ensure the completion of reproduction, guaranteeing the continuity of the human species, constituting fundamental and universal systems within human society. When discussing the functions of the reproductive system, Fei Xiaotong adopts the fundamental concept of his mentor Malinowski, that social institutions originate from human needs. However, regarding whether the marital and family system satisfies human biological needs or social needs, he puts forward a viewpoint different from Malinowski’s. This article also discusses the changes in Chinese marriage and family from the perspectives of the evolving social institutions of marriage and family, and the dynamics within family relationships.